Amine Borane Based Hydrogen Carriers: An Evaluation - Müller, Karsten; Stark, Katharina; Müller, Benjamin; Arlt, Wolfgang (Energy & Fuels, 2012)
Liquid organic hydrogen carriers (LOHCs) represent a new concept for energy-storage. LOHCs are able to store a considerable amount of hydrogen and release it on demand without being consumed themselves. A variety of different substances has been proposed recently. One promising group of potential carriers is amine borane based compounds. This contribution introduces the LOHC concept and gives a review over the amine borane based hydrogen carriers. An energetical evaluation using Aspen Plus was performed, and overall efficiencies were calculated. An energy storage system based on azaborines reaches efficiencies of up to 30%. This study shows that still intensive research on synthesis, regeneration, long-term stability, liquefaction, and toxicity is needed before this technique is marketable.

A new concept for the global distribution of solar energy: energy carrying compounds - Müller, Benjamin; Arlt, Wolfgang; Wasserscheid, Peter (Energy and Environmental Science, 2011)
A new concept for storage and superregional transport of solar energy from the earth's desert belt is proposed. The concept is based on solid alkaline earth metal compounds, showing an energy-rich and an energy-lean state which are used in an energy distribution cycle. The concept is evaluated with regard to overall solar-to-electricity efficiency and benchmarked by the overall efficiency of the DESERTEC concept. For a scenario assuming that the current share of electricity production from lignite coal in Germany is replaced by the here proposed concept, the CO(2) mitigation potential is calculated. The assessment shows that the proposed concept can compete with the benchmark and even shows high potential for optimization.

Energy Storage and Transportation Based on Solar Irradiation-Aided CaO-Looping - Obermeier, Jonas; Müller, Benjamin; Müller, Karsten; Arlt, Wolfgang (Energy Technology, 2015)

Energy Storage by CO2 Methanation and Energy-Providing Compounds: A Thermodynamic Comparison. - Müller, Benjamin; Müller, Karsten; Teichmann, Daniel; Arlt, Wolfgang (Chemie Ingenieur Technik, 2011)
Reconstructing current energy infrastructures dominated by fossil fuels towards a high share of renewable energy requires a drastic extension of energy storage capacities. Common storage technologies like compressed air or pumped water are either limited in capacity or have low efficiencies. A promising alternative is proposed with the use of energy carrying compds. for hydrogen storage. This route is shown to offer the possibility to combine high process chain efficiency with lossless energy storage for stationary and mobile applications. In this article, efficiencies for energy storage by methane and N-ethylcarbazole, and energy transport substances are calcd. and compared to each other. [on SciFinder(R)]
Keywords: Carbazole; Energy density; Energy transport substances; Hydrogen mobility; Hydrogen storage; Methanation; Storage efficiency